Hubungan Kepatuhan Pengobatan TB-RO terhadap Outcome Terapi Pasien Tuberkulosis di Rumah Sakit Muhammadiyah Lamongan: Correlation between Tuberculosis Drugs Resistence Treatment Compliance and Outcome of Tuberculosis Therapy Patients at Muhammadiyah Lamongan Hospital - Fauza Nisfu Laili; Devi Ristian Octavia; Muhtaromah Muhtaromah (Jurnal Sains dan Kesehatan, 2023)
Abstract Non-compliance with treatment will result in a high rate of failure in the outcome of therapy and result in the occurrence of Acid-resistant Bacilli that are resistant to standard treatment, causing unacceptable therapeutic outcomes to be achieved. This study was conducted with the aim of knowing the relationship between TB-RO treatment adherence to the therapeutic outcomes of tuberculosis patients at Muhammadiyah Lamongan Hospital. The research design uses a cross-sectional method. The population in this study were all RO-TB patients at Muhammadiyah Lamongan Hospital who came for treatment and were registered as patients at Muhammadiyah Lamongan Hospital, with a sample size of 30 patients. The sample selection was carried out using the Consecutive Sampling method. Data selection was carried out using the MARS-5 questionnaire and medical records. The data in this study were analyzed using the Chi-square test to determine the relationship between TB-pulmonary medication adherence to the therapeutic outcomes of tuberculosis patients at Muhammadiyah Lamongan Hospital. The results showed that the number of patients who had high medication adherence was 86.7% with a cured category of 83.3%. There is a significant relationship between TB-RO treatment adherence to the outcome of tuberculosis therapy in Muhammadiyah Lamongan Hospital with a p value <0.05 on the results of the Fisher's Exact Test. The higher the level of adherence, the higher the success rate of the therapeutic outcome obtained, but the lower the level of adherence, the lower the success rate of the TB-RO patient therapy. Kewords:             Treatment Adherence, Therapy Outcome, Drug Resistant Tuberculosis   Abstrak Ketidakpatuhan terhadap pengobatan akan mengakibatkan tingginya angka kegagalan pada outcome terapi dan mengakibatkan terjadinya Basil Tahan Asam yang resisten terhadap pengobatan standar sehingga menyebabkan outcome terapi yang diterima tidak tercapai. Penelitian ini dilakukan dengan tujuan untuk mengetahui hubungan antara kepatuhan pengobatan TB-RO terhadap outcome terapi pasien Tuberkulosis di Rumah Sakit Muhammadiyah Lamongan. Desain penelitian menggunakan metode cross-sectional. Populasi dalam penelitian ini adalah seluruh pasien TB-RO di Rumah sakit Muhammaadiyah Lamongan yang datang berobat dan sudah terdaftar sebagai pasien di RS Muhammadiyah Lamongan, dengan jumlah sampel 30 pasien pemilihan sampel dilakukan dengan metode Consecutive Sampling. Pemilihan data dilakukan menggunakan kuesioner MARS-5 dan Rekam Medis. Data pada penelitian ini dianalisis dengan uji Chi-square untuk mengetahui hubungan antara kepatuhan pengobatan TB-Paru terhadap Outcome terapi pasien Tuberkulosis di Rumah Sakit Muhammadiyah Lamongan. Hasil penelitian menunjukkan bahwa jumlah pasien yang memiliki kepatuhan pengobatan tinggi sebesar 86,7% dengan kategori sembuh sebesar 83,3%. Terdapat hubungan yang signifikan antara kepatuhan pengobatan TB-RO terhadap Outcome terapi pasien tuberkulosis di Rumah Sakit Muhammadiyah Lamongan dengan nilai p <0,05 pada hasil Uji Fisher’s Exact. Semakin tinggi tingkat kepatuhan akan semakin tinggi angka keberhasilan Outcome terapi yang didapatkan, namun semakin rendah tingkat kepatuhan akan semakin rendah angka keberhasilan Outcome terapi pasien TB-RO. Kata Kunci:         Kepatuhan Pengobatan, Outcome Terapi, TB-RO